1994
DOI: 10.1002/ajmg.1320520305
|View full text |Cite
|
Sign up to set email alerts
|

von Voss‐Cherstvoy syndrome: A variable perinatally lethal syndrome of multiple congenital anomalies

Abstract: We report 4 cases and review 7 from the literature with a pattern suggesting a variable early lethal multiple congenital anomaly syndrome. This was first reported by von Voss et al. [1979: "Klinische Genetik in der Pädiatrie," pp 70-74] and Cherstvoy et al. [1980: Lancet ii:485], and can affect upper limbs, face, brain, heart, lungs, urogenital and gastrointestinal systems, vertebrae and ribs, and can include thrombocytopenia. The initial cases had occipital encephaloceles and phocomelia, but milder cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…The presence of thumbs despite absent radii is a characteristic of TAR syndrome [Hall, 1987]. This finding was also present in our patient and in other von Voss-Cherstvoy syndrome patients [Cherstvoy et al, 1980;Bird et al, 1994;Lubinsky et al, 1994;Bamforth and Lin, 1997]. In contrast with von Voss-Cherstvoy, lower limbs are affected in about 50% of cases of TAR syndrome [Greenhalgh et al, 2002] and no brain malformations or sexual differentiation defects have been reported.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The presence of thumbs despite absent radii is a characteristic of TAR syndrome [Hall, 1987]. This finding was also present in our patient and in other von Voss-Cherstvoy syndrome patients [Cherstvoy et al, 1980;Bird et al, 1994;Lubinsky et al, 1994;Bamforth and Lin, 1997]. In contrast with von Voss-Cherstvoy, lower limbs are affected in about 50% of cases of TAR syndrome [Greenhalgh et al, 2002] and no brain malformations or sexual differentiation defects have been reported.…”
Section: Discussionsupporting
confidence: 84%
“…All reported cases have been sporadic and both sexes have been affected. Parental consanguinity reported by Lubinsky et al [1994] suggests an autosomal recessive pattern of inheritance. All previously reported cases of von Voss-Cherstvoy syndrome have had apparently normal chromosomes except for that described by Bamforth and Lin [1997] with mosaicism for a deletion of 13q12 in fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Voss-Cherstvoy Syndrome, and Cerebro-Cardio-Radio-Reno-Rectal ''Community'' DK-phocomelia (von Voss-Cherstvoy syndrome) [Lubinsky et al, 1994] comprises occipital encephalocele (OE) and a group of malformations similar to those of VACTERL-H (Table III). The comparison of the frequency of abnormalities in familial forms of VACTERL-H and in the DK-phocomelia syndrome shows the same spectrum and frequency of all studied congenital defects in both groups.…”
Section: David-o'callaghan Syndrome Vonmentioning
confidence: 99%
“…Infants with the syndrome described by von Voss and Cherstvoy, sometimes called DK-phocomelia syndrome, have been described with occipital defects only in conjunction with meningoencephaloceles [Cherstvoy et al, 1980;Lubinsky et al, 1994]. Kosaki et al described an infant with tetraphocomelia, severe ear and nasal hypoplasia, cleft palate and imperforate anus (Zimmer phocomelia) [Kosaki et al, 1996].…”
Section: Discussionmentioning
confidence: 99%